Homs' resistance to the Crusader invasion from its inception until the Battle of Hittin 491-583H / 1096-1187AD Dr. Noha Homa * Omaya Al gazzi - حميد, نهى; الغزي, أمية (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The phenomenon of the Crusades in the Middle Ages attracted wide interest from researchers in both East and West.The research deals with the resistance of Homs to the Crusade invasion until the Battle of Hittin 583 AH / 1187 CE.The research aims to highlight the military and political role that the city enjoyed during the Crusades era. The role of Homs and its participation in confronting the invasion from the Seljuk era to the era of Tughtakin and Bury, then the reign of Imad al-Din Zanki and his son Nur al-Din Mahmud and the time of Saladin. The reign of power in the Levant, And how the city had a prominent role in the assembly of Islamic armies in it, and the launch of the liberation of castles and forts and focus on the fortress of the Kurds and its role in the Islamic-Crusader conflict, which is one of the most important Crusader strongholds in the Levant contributed to stabilize their feet in the region, which could not be taken by Muslims for more than One hundred and seventy years, although they besieged him more than a dozen times, and this is due to the strength of the fort and the immunity of its fortifications.